Pengembangan Aplikasi Monitoring Tumbuh Kembang Bayi Usia Nol Hingga 24 Bulan berbasis Web - Rona Salsabila; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Children growth and development can increase significantly at the age of the first 1000 days of birth. Child growth and development can run optimally if the need for adequate nutritional intake. In early life, malnutrition (nutritional deficiencies) is very susceptible to occur, one of the consequences is stunting. Stunting is a condition when a baby has a lower height than a baby at his age, which is caused by poor parenting practices. The impact of a baby stunting can increase the risk of disease and even death, which will continue until the child is older. This application is formed by running 4 of the 5 stages of application development with the waterfall technique. Based on the results of the questionnaire, interviews with pediatricians and literature studies, 22 functional requirement were obtained and one non-functional requirement was obtained. Then the requirement modeling is done by using UML modeling which is used as a basis for implementing the design. The results of modeling are mapped into the PHP programming language, then tested with white box and black box techniques to test functional requirements and compatibility testing for non-functional testing. From the results of functional requirements's testing, obtained 100% valid results. While compatibility testing shows that the system is capable of running on 11 different search types.